Quantitative risk assessment of the effects of climate change on selected causes of death, 2030s and 2050s - Hales, Simon (World Health Organization, 2014)
Figures -- Tables -- Abbreviations -- Executive summary -- 1 Introduction and key findings Sari Kovats, Simon Hales, Simon Lloyd -- 1.1 Methods and data -- 1.2 Findings -- 1.3 Discussion -- 2 Heat-related mortality Yasushi Honda, Masahide Kondo, Glenn McGregor, Ho Kim, Yue-Leon Guo, Simon Hales, Sari Kovats -- 2.1 Background -- 2.2 Model development -- 2.3 Quantifying the association between temperature and mortality -- 2.4 Scenario data -- 2.5 Mortality -- 2.6 Adaptation assumptions projections -- 2.7 Results -- 2.8 Uncertainty -- 2.9 Discussion -- 3 Coastal flood mortality Simon Lloyd, Sari Kovats, Zaid Chalabi -- 3.1 Background -- 3.2 Quantifying the burden of flood-related disasters -- 3.3 Objectives -- 3.4 Description of the model -- 3.5 Scenario data -- 3.6 Assumptions -- 3.7 Results -- 3.8 Discussion -- 4 Diarrhoeal disease Sari Kovats, Simon Lloyd -- 4.1 Background -- 4.1.1 Sensitivity of diarrhoeal disease to climate variability and climate change -- 4.2 Description of model -- 4.2.1 Existing quantifications of the diarrhoea-temperature relationship -- 4.2.2 Model development -- 4.3 Scenario data -- 4.3.1 Climate data -- 4.3.2 Diarrhoea mortality projections -- 4.4 Assumptions -- 4.5 Results -- 4.6 Climate uncertainty -- 4.7 Discussion -- 4.7.1 Limitations of this study -- 5 Malaria Andreas Béguin, Joacim Rocklöv, Christofer Åström, Rainer Sauerborn, Valerie Louis, Simon Hales -- 5.1 Background -- 5.2 Description of the model -- 5.2.1 Malaria data -- 5.2.2 Climate data (observed) -- 5.2.3 GDP data -- 5.2.4 Population data -- 5.3 Estimating model parameters and validation -- 5.3.1 Final model -- 5.4 Scenario data -- 5.5 Results -- 5.5.1 Model parameters -- 5.5.2 Change in malaria risk in 2030 and 2050 -- 5.6 Population at risk of malaria -- 5.7 Discussion -- 6 Dengue Christofer Åström, Joacim Rocklöv, Andreas Béguin, Rainer Sauerborn, Valerie Louis, Simon Hales -- 6.1 Background -- 6.2 Description of the model -- 6.2.1 Dengue distribution data (observed) -- 6.2.2 Climate data (observed) -- 6.2.3 GDP and population data -- 6.3 Scenario data -- 6.4 Statistical analysis -- 6.4.1 Validation of model -- 6.5 Results: time periods and scenarios -- 6.5.1 Model -- 6.5.2 Population at risk -- 6.5.3 Projection of mortality -- 6.6 Discussion -- 7 Undernutrition Simon Lloyd, Sari Kovats, Zaid Chalabi -- 7.1 Background -- 7.2 Assessment method: linking crop, trade and health impact models -- 7.2.1 Step 1: national calorie availability estimates -- 7.2.2 Step 2: within-country food distribution estimates -- 7.2.3 Step 3: estimates of child stunting -- 7.2.4 Step 4: estimates of all-cause mortality attributable to stunting -- 7.3 Scenario data -- 7.3.1 Observed climate data -- 7.3.2 Climate scenarios -- 7.3.3 GDP and population projections -- 7.3.4 Scaling output for consistency with other health outcomes in the global assessment -- 7.4 Results -- 7.5 Regional estimates of children with stunting due to climate change -- 7.6 Mortality due to climate change-attributable undernutrition -- 7.7 Uncertainty -- 7.7.1 Parameter uncertainty in the health model -- 7.7.2 Uncertainty in stunting-attributable death -- 7.8 Discussion -- 8 Future worlds and scenario data Sari Kovats, Simon Lloyd, Sophie Bonjour, Colin Mathers -- 8.1 Introduction -- 8.2 Climate data: observed -- 8.3 Climate scenario data -- 8.4 Population projections -- 8.5 GDP data -- 8.6 Mortality projections -- 9 References -- Annex Definition of regions used in this assessment
Includes bibliographical references (pages 105-112). - Online resource; title from PDF cover (World Health Organization, viewed January 2, 2015)